PlastidHub: An integrated analysis platform for plastid phylogenomics and comparative genomics - Na-Na Zhang; Gregory W. Stull; Xue-Jie Zhang; Shou-Jin Fan; Ting-Shuang Yi; Xiao-Jian Qu (Plant Diversity)
The plastid genome (plastome) represents an indispensable molecular resource for studying plant phylogeny and evolution. Although plastome size is much smaller than that of nuclear genomes, accurately and efficiently annotating and utilizing plastome sequences remain challenging. Therefore, a streamlined phylogenomic pipeline spanning plastome annotation, phylogenetic reconstruction and comparative genomics would greatly facilitate research utilizing this important organellar genome. Here, we develop PlastidHub, a novel web application employing innovative tools to analyze plastome sequences. In comparison with existing tools, key novel functionalities in PlastidHub include: (1) standardization of quadripartite structure; (2) improvement of annotation flexibility and consistency; (3) quantitative assessment of annotation completeness; (4) diverse extraction modes for canonical and specialized sequences; (5) intelligent screening of molecular markers for biodiversity studies; (6) gene-level visual comparison of structural variations and annotation completeness. PlastidHub features cloud-based web applications that do not require users to install, update, or maintain tools; detailed help documents including user guides, test examples, a static pop-up prompt box, and dynamic pop-up warning prompts when entering unreasonable parameter values; batch processing capabilities for all tools; intermediate results for secondary use; and easy-to-operate task flows between file upload and download. A key feature of PlastidHub is its interrelated task-based user interface design. Give that PlastidHub is easy to use without specialized computational skills or resources, this new platform should be widely used among botanists and evolutionary biologists, improving and expediting research employing the plastome. PlastidHub is available at https://www.plastidhub.cn.